Coping strategies of nurses caring for mental health care users displaying violent and aggressive behaviour in mental health care institutions in North West province - Motlagomang Patience Sehularo; Annatjie van der Wath; Nombulelo Veronica Sepeng (Elsevier, 2024)
Background: Mental health care users displaying violent and aggressive behaviour is a serious concern in mental health care institutions. Nurses working in mental health care institutions are more exposed to patient violence compared to health care professionals in general health settings. However, there is limited evidence regarding the strategies used by nurses to cope with violent and aggressive behaviour in mental health care institutions, particularly in the North West province. Aim: The aim of the study was therefore to explore and describe the strategies used by nurses to cope with violent and aggressive behaviour in mental health care institutions in North West province. Methods: A qualitative-exploratory-descriptive and contextual research design guided the study. Face-to-face semi-structured individual interviews and field notes were used to collect data in August and September 2023 at two public mental health care institutions in North West which is one of the nine provinces in South Africa. The data was analysed by the researcher and an independent coder using thematic analysis. Results: Four themes emerged, namely: factors contributing to violence and aggression, negative experiences in caring for mental health care users displaying violent and aggressive behaviour, coping strategies used by nurses, and suggestions to enhance effective coping with violent and aggressive behaviour. Effective coping strategies mentioned by nurses include problem-focused coping strategies, appraisal-focused coping strategies and social-focused coping strategies. Conclusion: Although nurses had had negative experiences that affected their coping, they also shared effective coping strategies, namely faith-based practices, problem-focused coping strategies, appraisal-focused coping strategies, emotion-focused strategies and social coping.